Medullary Conus Topography in White-Tufted-Ear-Marmoset (Callithrix jacchus) - La Salles, Ana Yasha Ferreira de; Martins, Juliana Molina; Falcão, Brunna Muniz Rodrigues; Santos, José Rômulo Soares Dos; Medeiros, Guildenor Xavier; Menezes, Danilo José Ayres De (Acta Scientiae Veterinariae, 2017)
Background: The common marmoset (Callithrix jacchus) belongs to the family Cebidae and Subfamily Callitrichinae, a group formed by the smallest anthropoid primates. It is a very common species and adapts easily to captivity, an aspect that encourages the clandestine capture of these animals and makes them susceptible to wounds resulting from clandestine rearing and inadequate management, so that studies to understand the species are extremely important. With the objective of supplying anatomic bases for the practice of epidural anesthetic, data were studied regarding the topography of the common marmoset (Callithrix jacchus). Materials, Methods & Results: The study was carried out at the Laboratory of Veterinary Anatomy at the Federal University of Campina Grande (UFCG), PA, Brazil. Ten adult common marmosets (Callithrix jacchus) were used, 5 males and 5 females, with different causes of death. A round workbench magnifying lamp was used to better visualize the dissecation field. Number 15 scalpel blades, surgical pincers and scissors were used to dissect. After fixing in 10% formaldehyde aqueous solution, dissecation was made along the mid dorsal line, from the cranial thoracic region to the tail base to expose the vertebral arches and measure the intervertebral spaces. The vertebral arches were removed, and consequently the spinal dura mater was exposed, that was sectioned longitudinally to expose the spinal chord and identify the lumbar intumescence, the conus medullaris and the cauda equina. The length of the conus medullaris was measured and its skeletopy was established. The body and tail length data were submitted to analysis of variance and the means were compared by the Tukey test at 5% probability. The mean value of the conus medullaris length was 1.4 cm, while the anatomic location of the conus medullaris varied slightly among the animals, but did not pass the limit between L3 for the base and L6 for the apex. On average, the lumbosacral space measured 3.03 mm, that is sufficient to introduce a needle similar to that used in syringes for insulin injection. The results of this study suggest the lumbarsacral space as location for epidural anesthetic application in Callithrix jacchus, at a safe point situated in the center of an isosceles triangle, the base of which is found when a line is drawn from one side of the pelvis to the other, and the apex corresponds the spinal process of the first sacral vertebra. Discussion: The anatomic location of the conus medullaris is different compared to two other primate species, the red handed tamarin (Saguinus midas), in which the cone base was registered at L4 and the apex at S2, and the common squirrel monkey (Saimiri sciureus) where the conus medullaris base occurs at L7-8 and the apex at S3 or Cc1. However, some similarities with other mammal groups were observed in the conus medullaris topography, such as the black-striped capuchin (Sapajus libidinosus). The mean conus medullaris length of the species Callithrix jacchus of 1.4 cm was close to that observed in the coypu, capuchin monkey and sloth, and significantly smaller than the means obtained for the red handed tamarin and common squirrel monkey and other non-primate mammals reported in the literature. The lumbosacral space is the location indicated for epidural anesthesia in Callithrix jacchus, that has also been indicated for other wild mammals such as the black-striped capuchin monkey (Sapajus libidinosus), the maned wolf (Chrysocyon brachyurus), the tayra (Eira barbara), the giant otter (Pteronura brasiliensis), the crab-eating racoon (Procyon cancrivorus) and the coypu (Myocastor coypus).